(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The aim of the research is to observe the activities of the students in academic speaking classroom, to analyze the student’s problem in presenting the academic speaking presentation and to identify the student’s special needs in academic speaking presentation.The method used in this research is field research that is qualitative, while the analysis of the data used descriptive analysis. The focus of the research is on the student’s difficulties in presenting academic speaking presentation.